From Political Contracts to Policies: Clientelistic or Programmatic? - Rahman, Aldhayavira Julia; Ardiansa, Dirga (UI Scholars Hub, 2022)
Community Action Plan (CAP) is a priority program of the governor in structuring residential areas use a collaboration method with the society, both in planning and implementation of development. This program is regulated through Governor Decree Number 878 of 2018 and Governor Regulation Number 90 of 2018. However, before it became a public program and policy, the initial formation of the CAP program came from a political contract agreed by members of the JRMK (Jaringan Rakyat Miskin Kota) with Anies Baswedan ahead of the 2017 local elections, to encourage efforts a winning number of polling stations in the JRMK working area. Due to this process, an assumption appear that the CAP program was a clientelistic because it was a compensation for support in the local elections which would only partially benefit to JRMK and did have not basic regulations as a legal policy. This research reveals a transformation existence of the allocation process and distribution of resources from clientelistic towards programmatic. The results of this research show that the form of distributive politics between clientelistic and programmatic is not always black-and-white (Stokes, Dunning, Nazareno, & Brusco, 2013) or gray (Savirani & Aspinal, 2017) but there can also be a shift in form. In addition, it also was found that the presence of Presidential Decree Number 16 of 2018 about the Procurement of Goods and Services open some opportunities for collaboration between local governments and community groups. Organizing carried out by the companion groups has a role in driving this transformation effort.